Action Mechanisms and Therapeutic Targets of Renal Fibrosis - Ma Shi-Xing; Shang You-Quan; Zhang Huan-Qiao; Su Wei (Journal of Nephrology Advances, 2018)
Renal fibrosis was a chronic and progressive process affecting kidneys in chronic kidney disease (CKD), regardless of cause. Although no effective targeted therapy yet existed to retard renal fibrosis, a number of important recent advances have highlighted the cellular and molecular mechanisms underlying the renal fibrosis. The advances including TGF-β/Smad pathway, oxidative stress and inflammation, hypoxia and gut microbiota-derived from uremic solutes were highlighted that could provide therapeutic targets. New therapeutic targets and strategies that are particularly promising for development of new treatments for patients with CKD were also highlighted.
Keywords: chronic kidney disease